Sistema de proteção adaptativa - Silva, Kathiane Queiroz da (2014)
This paper proposes an adaptive protection system (SPA) developed in Matlab, in order to make the smart grid for greater flexibility reliability and security of the electric power system the protection system proposed is able to assist in the study of protection by the choice of settings to be entered in the relay once the mains relays are parameterized adaptive protection is responsible for discerning between a change of setting group or send new settings this decision is taken by the SPA in the control center and sent to the grid relays in real time the SPA was tested in a medium voltage distribution grid and the sending of change protection setting was validated using SEL-751 relay using communication via Telnet based on testing the proposed SPA acted properly ensuring selectivity and coordination of the protection system